Bantenologi’s Biographies of Ulama and Religious Leaders in Banten 1810-2000 (Kawalu: Journal of Local Culture, 2024)
Laboratorium Bantenologi has currently conducted research and written the biographies of ulama (teachers of Islamic knowledge) and religious leaders in Banten who lived between 1810-2000. The Laboratorium have categorized a number of certain criteria for the ulama to be included in the biographies which are deemed significant in the nomination process. Such criteria are 1) the genealogy of science (specialization and field of science), 2) the period, 3) the typology and the institution of teaching, 4) intellectual (academic) careers and or politics, and 5) their legacy (works, organizations and thoughts). Furthermore, the biographies will be a part of a (bigger) book project called Encyclopedia of Indonesian Ulama and Religious Leaders